Riwayat Isrāiliyyāt - Mukarromah; Rika Sartika (Al-Jadwa: Jurnal Studi Islam, 2022)
Efforts to interpret the Qur'an have never stopped being carried out by Muslims. Awareness of the importance of understanding the Qur'an motivates mufassir to interpret the verses of the Qur'an. In addition, with the interpretation, scientific insights are increasingly developing from generation to generation to help various problems in human life. Thus the existence of the Qur'an will always be preserved. The interpretation of the Qur'an was carried out during the time of the Prophet Muhammad saw. The Qur'an handed down by Allah is understood, interpreted, and explained by the Messenger of Allah to the companions. After the Prophet died, the companions had difficulty understanding the verses of the Qur'an related to past events. However, there are Muslims who were previously Jews and Christians (ahlu kitab) who knew of past events. The events they presented for the interpretation of the Qur'an are what is called the history of isrāiliyyāt. In the development of interpretation, it is known that many of the books of interpretation multiply the history of isrāiliyyāt. History is taken to explain the meaning of the verses of the Qur'an. In addition to clarifying understanding, sometimes mufassir deliberately cites the history of isrāiliyyāt for criticism. There are even mufassir who like to take the history of isrāiliyyāt because mufassir is also a muballigh. Regarding the historical law of isrāiliyyāt, some scholars accept, and some refuse. However, some opinions can mediate between the two. It is explained that if the history of isrāiliyyāt corresponds to shari'a, then it can be taken. If the history does not correspond to shari'a it is forbidden to take it. Whereas if the history of isrāiliyyāt is silenced by shari'a, then it is not punished by anything.